Apoptotic Effect of Gemini Curcumin on MDA-MB-468 Breast Cancer Cell Line - Hajizadeh, Masoumeh; Ghoran, Salar H.; Azeez, Hewa Jalal; Feizi, Mohammad A. H.; Babaei, Esmaeil (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Gemini Curcumin (Gemini-Cur) is the latest nanoformulation of curcumin with a significant apoptotic effect on cancer cell lines. Objective: This in vitro study aims to evaluate the apoptotic effects of Gemini-Cur toward MDA-MB-468 breast cancer cell lines and further the related mechanism of apoptosis. Methods: The cytotoxicity of Gemini-Cur toward MDA-MB-468 cell lines was tested using MTT assay. Furthermore, the expression ratio of Bax/Bcl-2 was evaluated by qRT-PCR. Consequently, the protein expression of Bax/Bcl-2, survivin, and caspase-3 was measured using western blotting. Results: Having treated MDA-MB-468 cell lines with Gemini-Cur, the IC50 values were found to be 44.44 and 31.63 μM at 24 and 48 h, respectively. Our findings showed that Gemini-Cur significantly suppresses cancer cell proliferation in a time- and dose-dependent manner. Furthermore, the data revealed that curcumin nanoformulation induces apoptosis in MDA-MB-468 cells through modulation of the expression of Bax, Bcl-2, Survivin, and Caspase-3. Conclusion: The data of the current study propose that Gemini-Cur can be considered a promising candidate against triple-negative breast cancer.
Keywords: Apoptosis